Vielfalt als Wettbewerbsfaktor nutzen: Diversity Management in Hamburg; Ergebnisse einer Unternehmensbefragung - Martin Klaffke (Hamburg School of Business Administration (HSBA), 2008)
The study analyses the application of Diversity Management among companies of the Free and Hanseatic City of Hamburg and elaborates differences between small and medium-sized as well as large companies. The results indicate that Hamburg companies are not extensively familiar with the concept Diversity Management and that practical application is only limited so far. In addition, large companies seem to be ahead of small and medium-sized companies in conceptual design and implementation of Diversity Management. Nearly all companies participating in the study have introduced first measures supporting Diversity among employees. However, the measures' strategic impact and adequacy to build competitive advantage are questionable, as companies rarely engage in Diversity Management controlling. Capitalizing on employee diversity will often require a long-term cultural transformation process. As an integrative approach the study suggests the 3-S-Diversity Management Model. It offers a conceptual framework to trategically implement Diversity Management and therefore to cope with the concept's practical weaknesses identified in the study.
Keywords: 650; Diversity Management; Competitive Advantage; Small and Medium-sized Companies